Penilaian Gereja Katolik Terhadap Perkawinan Tanpa Anak - Blasius Superma Yese; Alexius Poto; Noberta Nadia Waruwu (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
Since the beginning of creation, as written in the Book of Genesis, God created men and women who were united in marriage. One of God's commands to them is to reproduce. In the Church doctrine it is further outlined that one of the purposes of marriage is the good of the child (bonum prolis). One of the important points in this concept is the openness of married couples to accept the presence of children in their marriage. In contrast to the Church doctrine above, nowadays there are married couples who have taken the stance of refusing to have children in marriage. This reality is known as childfree. With the freedom, humans feel they have the right to reject God's great plan for married life. There are various reasons for choosing childfree, including: personal, medical, economic and environmental reasons. The Catholic Church in principle rejects the childfree movement, because it is contrary to God's plan for marriage.